Genetic Diversity of Colletotrichum spp. an Endophytic Fungi in a Medicinal Plant, Brazilian Pepper Tree. (30th May 2012) - Lima, J. S.; Figueiredo, J. G.; Gomes, R. G.; Stringari, D.; Goulin, E. H.; Adamoski, D.; Kava-Cordeiro, V.; Galli-Terasawa, L. V.; Glienke, C.
Abstract : In this study, we reported thirty-nine endophytic fungi identified as Colletotrichum spp. associated with Brazilian pepper tree or aroeira ( Schinus terebinthifolius Raddi. Anacardiaceae) in Paraná state, Brazil. These endophytes were identified by morphological and molecular methods, using PCR taxon-specific with Ca Int/ITS4, Cg Int/ITS4, and Col 1/ITS4 primers, which amplify specific bands in C. acutatum, C. gloeosporioides lato sensu, and Colletotrichum boninensis, respectively, and by DNA sequence analysis of the nrDNA internal transcribed spacer region (ITS1, 5.8S, ITS2). We also assayed the presence of dsRNA particles in Colletotrichum spp. isolates. Combining both morphological characters and molecular data, we identified the species C. gloeosporioides, C. boninense, and C. simmondsii . However, we found a high genetic variability intraspecific in C. gloeosporioides which suggests the existence of several other species. Bands of double-stranded RNA (dsRNA) were detected in three of thirty-nine isolates. Identity of these bands was confirmed by RNAse, DNAse, and S1 nuclease treatments for the isolates LGMF633, LGMF726, and LGMF729. This is the first study reporting these particles of dsRNA in C. gloeosporioides .